2022
DOI: 10.3390/met12010113
|View full text |Cite
|
Sign up to set email alerts
|

Split-Plot I-Optimal Design Optimisation of Combined Oil-Based and Friction Stir Rotation-Assisted Heating in SPIF of Ti-6Al-4V Titanium Alloy Sheet under Variable Oil Pressure

Abstract: The aim of this paper is to determine the optimal input parameters for the process in order to ensure the maximum formable wall angle is obtained in a conical frustum with a varying wall angle fabricated using Single Point Incremental Forming (SPIF). The test material was 0.8-mm-thick Ti-6Al-4V titanium alloy sheets, and the test used a tungsten carbide tool with a rounded tip with a radius of 4 mm. Complete workpieces were heated using hot oil with a temperature of about 200 °C, and in addition, the high rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Trzepiecinski et al [19] focused on the sheet manufacturing of a Ti6Al4V alloy, in terms of a single-point incremental forming (SPIF) experiment and using a grease-free dry anti-friction spray of MoS 2 as the lubricant. They determined the optimal input processing parameters during warm SPIF of a Ti6Al4V sheet with an initial thickness of 0.8 mm based on a split-plot I-optimal design to ensure the maximum formable wall angle.…”
Section: Contributionsmentioning
confidence: 99%
“…Trzepiecinski et al [19] focused on the sheet manufacturing of a Ti6Al4V alloy, in terms of a single-point incremental forming (SPIF) experiment and using a grease-free dry anti-friction spray of MoS 2 as the lubricant. They determined the optimal input processing parameters during warm SPIF of a Ti6Al4V sheet with an initial thickness of 0.8 mm based on a split-plot I-optimal design to ensure the maximum formable wall angle.…”
Section: Contributionsmentioning
confidence: 99%
“…The long processing time compared to conventional forming makes incremental forming methods suitable for small batch sheet metal forming operations [21]. SPIF can be performed under cold and hot conditions using heat blowers [22], frictional heat generated by tool rotation [23] and liquid heating [24].…”
Section: Introductionmentioning
confidence: 99%
“…An established numerical model has not been found in the literature to the best of our knowledge. A finite element-based numerical model build in Abaqus/Explicit took into account the experimental parameters presented in the authors' previous article [24]. This article focuses on the numerical analysis of deformations and forming forces for the optimal set of SPIF process parameters experimentally obtained in [24].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature [2] on SPIF of titanium and titanium alloy sheets showed that there are insufficient investigations into the synergistic effect of rotational speed and tool rotation direction on the surface roughness of SPIFed drawpieces. In another previous paper, [43], the authors applied a split-plot I-optimal design to optimise combined oil-based and friction stir rotation-assisted heating in SPIF of Ti-6Al-4V sheets. It was concluded that step size is the most significant factor that affects the in-plane forming force.…”
Section: Introductionmentioning
confidence: 99%